Impact if Chlorpyrifos on the Second Instar Mosquito Larvae as Bioindicator in El-Beheira Governorate, Egypt - E. Eissa, Ebrahim; Radwan, EH; Abdel Hakeem, N; Abdel Aziz, KK; Hashem, HO; Radwan, K.H. (International Journal of Limnology, 2020)
Pesticides are the major source of concern as water pollutants. Chlorpyrifos (CPY) (O,O-diethyl-O-(3,5,6-trichloro-2-pyridinyl) phosphorothioate; CAS No. 2921-88-2). CPY is a widely used organophosphate insecticide. The aim of current study was to determine the effects of CPY on the second instar larvae of Culex mosquito as a bio-indicator of water pollution. Levels of CPY in stream water was evaluated. Toxicity of CPY was estimated on mosquito. Along with the evaluation of effects of water polluted with CPY on mosquito to predict the water pollution levels. Results showed that LC95 of CPY was 6331.30 mg/kg after 24hr and increased to 230506.4 ppm after 48hr of exposure. It was noted that the activity of CPY is concentration and time dependent. The 0.09 ppm concentration of CPY (the amount that was found in the stream water) had no effect on the second instar Culex larvae similar to the control (tap water). There is no effect after 72,96h of exposure of the population to the detected insecticide. It could be concluded that mosquito is not a bioindicator of CPY pollution at the detected level in stream water.
Keywords: Chlorpyrifos; Mosquito Larvae; Culex; Water Pollution; Bioindicator; Organophosphate Insecticide; Second Instar